Continuous-flow electron spin resonance microfluidics device with sub-nanoliter sample volume - Oleg Zgadzai; Nir Almog; Yefim Varshavsky; Moamen Jbara; Benoit Driesschaert; Aharon Blank (Journal of Magnetic Resonance Open, 2025)
This paper presents a novel continuous-flow electron spin resonance (ESR) microfluidic device designed for both continuous-wave (CW) and pulsed ESR measurements on sub-nanoliter liquid samples. The system integrates a planar surface microresonator (ParPar type) operating at ∼9.4 GHz with a precision-fabricated quartz microfluidic chip, enabling spatial confinement of the sample within the resonator’s microwave magnetic field hotspot while minimizing dielectric losses. The effective sample volume is ∼0.06 nL, and the device supports standard microfluidic connectors, facilitating both continuous and stopped-flow experiments. Using a 1 mM aqueous solution of deuterated Finland trityl (dFT) radical, CW ESR measurements yielded a peak signal-to-noise ratio (SNR) of ∼83 for a 100-point spectrum acquired over 80 s, with a resonator quality factor of Q ∼15–20. This corresponds to a spin sensitivity of ∼1.04 × 109 spins/√Hz/G. Pulsed ESR measurements, performed with 0.1 W microwave power and 10 ns π pulses, achieved an SNR of ∼47 with 1 s of averaging, corresponding to a spin sensitivity of ∼7.8 × 108 spins/√Hz. A Rabi frequency of ∼50 MHz was measured, indicating a microwave conversion efficiency of ∼56 G/√W. Both the pulsed spin sensitivity and Rabi frequency are consistent with simulated values. This device represents a significant step toward ESR-based detection of individual, slowly flowing cells—analogous to flow cytometry but with magnetic resonance contrast. With future enhancements such as higher operating frequencies, cryogenic integration, or optimized resonator geometries, the system is expected to enable practical ESR measurements at the single-cell level.